New trends in antithrombotic therapy in vascular neurology - E. A. Shirokov (Лечащий Врач)
In recent years, for the first time in developed economies and high-income countries, a reduction in the incidence of stroke has been achieved. The trend towards a decrease in cardiovascular morbidity in economically developed countries of the world proves the effectiveness of a preventive strategy based on the modification of the main risk factors and the use of modern drugs (antihypertensive, hypolipidemic and antithrombotic). The success of preventive medicine is associated with new medical technologies and new more effective drugs – anticoagulants and antiplatelet agents. Antithrombotic therapy for the prevention of the first or repeated stroke is the most important area of primary and secondary prevention of cardiovascular diseases. The author summarizes and analyzes new trends in antithrombotic therapy in clinical practice. The main changes in the antithrombotic strategy relate to the primary prevention of stroke, management of patients with transient ischemic attacks, and early secondary prevention.